Revisiting regulatory T cells as modulators of innate immune response and inflammatory diseases - Ou, Qifeng; Power, Rachael; Griffin, Matthew D. (Frontiers in Immunology, 2023)
Regulatory T cells (Treg) are known to be critical for the maintenance of immune homeostasis by suppressing the activation of auto-or allo-reactive effector T cells through a diverse repertoire of molecular mechanisms. Accordingly, therapeutic strategies aimed at enhancing Treg numbers or potency in the setting of autoimmunity and allogeneic transplants have been energetically pursued and are beginning to yield some encouraging outcomes in early phase clinical trials. Less well recognized from a translational perspective, however, has been the mounting body of evidence that Treg directly modulate most aspects of innate immune response under a range of different acute and chronic disease conditions. Recognizing this aspect of Treg immune modulatory function provides a bridge for the application of Treg-based based therapies to common medical conditions in which organ and tissue damage is mediated primarily by inflammation involving myeloid cells (mononuclear phagocytes, granulocytes) and innate lymphocytes (NK cells, NKT cells,  T cells and ILCs). In this review, we comprehensively summarize pre-clinical and human research that has revealed diverse modulatory effects of Treg and specific Treg subpopulations on the range of innate immune cell types. In each case, we emphasize the key mechanistic insights and the evidence that Treg interactions with innate immune effectors can have significant impacts on disease severity or treatment. Finally, we discuss the opportunities and challenges that exist for the application of Treg-based therapeutic interventions to three globally impactful, inflammatory conditions: type 2 diabetes and its end-organ complications, ischemia reperfusion injury and atherosclerosis.